Universitas Nasional Lecturer Attendance System Design Using Web-Based Low Fidelity Prototype Method - Sultana Namira; Agung Triayudi; Endah Tri Esti Handayani (Jurnal Mantik, 2020)
The Universitas Nasional Lecturer Attendance Website is a web-based application that functions for lecturers to do attendance while the lecturer or admin secretariat can validate the attendance of the lecturer if the lecturer is not present because he is unable to input attendance. On the website, there are several features that can be used by users, including student features, lecturer features, and admin features. students can update their profile and can ask questions to academics through the contact us feature. Likewise, lecturers and admins will validate the absences of lecturers in the admin feature. This can make it easier for the admin to go through the database. In addition, this website can make it easier for admins in terms of archiving / recapping data because the system is connected directly through the database.